Cryptosporidium: Ultrastructural examination of jejunal biopsy - (:unkn) unknown (My University, 1996)
The present case report describes a 6-year-old boy with cellular immunodeficiency who developed cryptosporidiosis of the jejunum. The patient had been admitted to the hospital with abdominal pain, diarrhea, nausea, jaundice and respiratory disorders. Pathological work-up of the intestinal biopsy revealed cryptosporidiosis, which was confirmed by transmission (TEM) and scanning electron microscopic (SEM) examinations. Both the SEM and TEM examinations showed that a large number of cryptosporidia were loosely attached to the brush border of intestinal cells. The extracytoplasmic membrane bounded microorganisms were shown to inhibit the microvillar structure at the attachment zone of the epithelial cells of the intestines. In addition to this usual localization, a second type of localization of parasite was also identified deep within the cytoplasm of the intestinal cells. In chronic diarrhea of unknown origin, the examination of jejunal biopsy material is also an important investigational tool as shown in this study. Despite the presence of chronic diarrhea, there was no obvious alteration in the histological architecture of the jejunum but we were able to detect the presence of the parasite in the biopsy material in two different localizations. To confirm the pathologic findings, a high resolution microscopic technique can be used. It is a sensitive technique both for providing evidence for the presence of the infection and detecting the localization of the parasite, especially at an unusual localization, which could otherwise not have been discovered by routinely available techniques.
Keywords: Cryptosporidiosis; Jejunum; Ultrastructural examination